Réforme du curriculum et approche par compétences au Cap Vert. Entre injonction internationale et projet national ? - Ana Cristina Pires-Ferreira (Les éditions de la Maison des sciences de l'Homme, 2014)
This article aims to analyze the curriculum reform in Cape Verde, a small country situated off the West-African coast, which attempts to introduce competency-based education (CBE) as a solution to the quality deficit in basic and secondary education. This deficit is seen to be expressed by the weak relevance of the curriculum and its non-alignment with societal needs and educative innovations put forward by international organizations. The main question is: to what extent is the curriculum reform centered on competency-based education the reflection of a reconciliation between national interests and international alignment? To answer this question we analyze why and how the CBE has been introduced into the curriculum policy in Cape Verde and we look at the current state of its implementation. The approach is sociopolitical and the analysis is based on the political, institutional and technical discourses, as well as on the discourses of the various actors participating in the current curriculum reform which is implemented since 2006.